Peran Humas dalam Pengembangan Citra Sekolah melalui Link dan Match dengan Industri Dunia Kerja dalam Penyerapan Alumni di SMK Negeri 1 Lawang Wetan - Yusneti, Yusneti; Viona, Elsa (Journal of Innovation in Teaching and Instructional Media, 2021)
Departments must match alumni and prospective alumni's skills so that the industrial world can be absorbed and alumni can begin working immediately according to the company and their skills. This study aimed to determine the role of public relations in the absorption of alumni and prospective alumni at SMK Negeri 1 Lawang Wetan through links and matches with the world of the work industry. The findings revealed that SMK Negeri 1 Lawang Wetan's Special Job Exchange played an important role in assisting alumni in finding jobs. The Special Job Exchange has put together a number of work programs to carry out its function of putting alumni in order to reach the absorption of alumni and boost the reputation of SMK Negeri 1 Lawang Wetan.